Analisis Podcast Close The Door Tentang Pelanggaran Etika Episode Catheez - Iqbal Syaefulloh; Elsa Melinda; Raden Arla Syamira Putri; Samuel Tulus Hati Karo Karo; Ahmad Alfha Risi; Raihan Firdaus Naufal (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
The purpose of this research is to conduct an analysis of possible ethical violations contained in the episode